AGRONOMIC PERFORMANCE OF COTTON AND SOYBEAN CULTIVATED UNDER DIFFERENT COVER CROPS AND LIME AND GYPSUM DOSES - Benart, Leila [UNESP]; Roque, Cassiano Garcia; Silva Campos, Cid Naudi; Prado, Renato de Melo [UNESP]; Vilela, Rafael Goncalves [UNESP]; Teodoro, Paulo Eduardo (Univ Federal Uberlandia, 2020)
Soil management with the use of lime and agricultural gypsum can influence the development and yield of cotton and soybean crops. The use of cover crops avoids soil degradation and ensures nutrient cycling on the soil surface. In most cultivated species, the application of lime and agricultural gypsum provides corrections in the sub-surface soil, keeping the nutrients available. This study aimed to (i) verify whether cotton and soybean cultivated in succession to cover crops affect its agronomic performance and (ii) evaluate the influence of lime and gypsum doses on the agronomic performance of these crops. Two experiments were performed. The first experiment consisted of cotton cultivated in the off-season, and the second, of soybean cultivated in the regular season. The experiment was carried out under three plant residues (Urochloa ruziziensis, Pennisetum glaucum, and fallow area), combined with lime and gypsum doses. The experiment consisted of a completely randomized block design with four replications. For the cotton crop, only the gypsum doses influenced the variables plant height, initial and final population, and yield. Cover crops did not influence the agronomic performance of cotton and soybeans. The increase of lime doses resulted in a linear increase in cotton and soybean yield. The highest gympsum dose improved the agronomic performance of cotton plants; however, it only influenced the height of soybean plants.
Keywords: Plant residues; Glycine max; Gossipium hirsutum; Green manure